REMEDIASI MISKONSEPSI PESERTA DIDIK MENGGUNAKAN MODEL PBL PADA MATERI GETARAN DI SMP - Solihah, Gina Suryani; Sitompul, Stepanus Sahala; Oktavianty, Erwina (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe purpose of this research is to know the effectivity of the Problem Based Learning (PBL) design to remediate the misconceptions of the students toward oscillation subject. This study used quasy-experimental research with pretest-posttest control group design which 63 students participated at the VIII grade in SMPN 2 Sungai Raya, which was taken by cluster random sampling. The data was taken by 15 multiple choice open-ended questions. The average of the reduction of the misconceptions in the experimental class was 51.99%, whereas in control group was 14.38%. Based on U Mann-Whitney with significance 5%, showed that there was a significant difference between the PBL design and conventional design to remediate the student’s misconceptions in oscillation. PBL design is effective in remediating the student’s misconceptions in oscillation with effect size score in 2.31 which is categorized high enough by Cohen. So the PBL design can be used as the alternative design for remediating the misconceptions. Keyword: Remediation, Problem Based Learning, Oscilation